Cytotoxicity of oleandrin isolated from the leaves of Nerium indicum Mill. on several human cancer cell lines - Mae S.H. Wahyuningsih; Sofia Mubarika; R.L.M. Bolhuis; K. Nooter; Ibnu G. Gandjar; Subagus Wahyuono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Finding anticancer drugs from natural resources still proceeds. Oleandrin isolated from Nerium indicum Mill. inhibited the growth of mieloma cell line in vitro better than that of vincristine sulphate. This study was aimed to determine the cytotoxic effect of oleandrin on various human cancer cell lines. Cytotoxic test of oleandrin on seven human cancer cell lines was done by SRB-method. The analysis was conducted by comparing the ID50 of oleandrin with that of doxorubicin and cisplatin as positive controls. This result indicated that oleandrin possessed the best cytotoxic effect on breast cancer (MCF7) with ID50 at 8.85 nM. Keywords : Oleandrin, cytotoxicity, human cancer cells, ID50